El Tribunal Constitucional como poder autónomo en el sistema colombiano - Tarapués Sandino, Diego Fernando (2023)
This article is a brief journey to the institutional location that the Constitutional Court has, and to the one it should have, within a Constitutionís political or instrumental structure, particularly in the Colombian case. The article can be divided in four parts: first, an overview of the principles of the supremacy of the Constitution and the division of powers is presented, in order to point out who, historically, the defenders of the Constitution have been. Second, the author reflects openly on where the Constitutional Court should be. Third, the article performs a comparative legal analysis of where the Constitutional Court is located in different South American legal systems. Finally, some conclusions are proposed, whose main thrust is the idea of emancipating the Colombian Constitutional Court from the judicial branch.